Partnership is key to fight hunger and achieve food for all - Wall, Gavin (Indian Farming, 2015)
An estimated 925 million people around the world—almost one-sixth of all humanity—are suffering from hunger today. A staggering 578 million people are undernourished in Asia alone. Two thirds of the world’s undernourished lie in just seven countries—Bangladesh, China, the Democratic Republic of Congo, Ethiopia, India, Indonesia and Pakistan. About 40% of world’s absolute poverty is in South Asia making it a global hotspot of poverty.